Effect of coping materials zirconia or polyetheretherketone with different techniques of fabrication on vertical marginal gap and fracture resistance of posterior crowns with composite veneering - Marwa Emam; Mohamed F. Metwally (BMC, 2023)
Abstract Background Insufficient research has been conducted in the literature assessing the performance of zirconia and polyetheretherketone (PEEK) crowns in relation to the essential requirements of successful restorations, such as fracture resistance or margin adaptation. The purpose of this study was to evaluate the effect of the coping materials zirconia or PEEK with different fabrication techniques on the vertical marginal gap and fracture resistance of posterior crowns with composite veneering. Methods Ceramic copings (n = 18) restoring mandibular first molar were fabricated from zirconia (Zircon.x, Presidentdental, Germany), milled PEEK (PEEK CAD) (breCAM.BioHPP, Bredent, Germany) and pressed PEEK (PEEK Press) (BioHPP Granules, Bredent, Germany) six specimens each (n = 6). The copings were veneered with high impact polymer composite (HIPC) material (breCAM.HIPC, Bredent, Germany). The vertical marginal gap was captured under a magnification of 40X. Five equidistant marks on each surface of the die distinguished the points of measurement for a total of 20 readings per sample. The analysis was completed using an image analysis system (ImageJ 1.53t, National Institute of Health, USA). The specimens were loaded to failure at a crosshead speed of 1 mm/min and the load at failure was recorded to measure the fracture resistance. Results The marginal gap was analyzed using one-way ANOVA followed by Tukey's post hoc test. Fracture resistance was analyzed using Welch one-way ANOVA followed by the Games-Howell post hoc test. Marginal gap values showed a significant difference between the tested groups, with zirconia having significantly lower gap values (48.67 ± 11.98 µm) than both the PEEK CAD (108.00 ± 20.08 µm) and Press groups (108.00 ± 25.10 µm) (p < 0.001). However, the results of fracture resistance showed no significant difference (p = 0.06) with 1687.47 ± 253.29 N, 2156.82 ± 407.64 N, 2436.72 ± 725.93 N for zirconia, PEEK CAD, and Press, respectively. The significance level was p < 0.05. Conclusions Zirconia framework crowns have a smaller vertical marginal gap than milled and pressed PEEK crowns. Crowns fabricated from zirconia, PEEK CAD, or PEEK Press frameworks and veneered with composite resin have comparable fracture resistance lower than the maximum biting force in the posterior region. Clinical relevance Posterior crowns with zirconia frameworks are preferred over milled and pressed PEEK frameworks regarding margin adaptation, although all can safely survive the maximum occlusal forces without fracture.